Design, Development, and Evaluation of an Interwoven Electrospun Nanotextile Vascular Patch. Issue 11 (16th July 2021) - Babu, Rosebin; R, Reshmi C; Joseph, John; Sathy, Binulal N.; Nair, Shantikumar V.; Varma, Praveen Kerala; Menon, Deepthy
Abstract: This study details the design and fabrication of woven electrospun nanotextile patches for vascular applications that meet the mechanical and biological requirements. Nanotextile vascular patches based on biodegradable polymers such as poly‐l ‐lactic acid (PLLA) and poly(caprolactone)/collagen (PCL/Col) are fabricated by integrating the techniques of electrospinning and weaving. Fibrous polymeric nanoyarns obtained by electrospinning are strengthened via different postprocessing techniques of heat‐stretching and plying, to generate interwoven nanotextiles that are tightly packed, mechanically strong, yet flexible. The unique pattern of nanofibers within the nanotextile results in its exceptional anisotropic mechanical behavior, appropriate for a vascular patch material. Moreover, these matrices exhibit good hydrophilicity, protein adsorption, and hemocompatibility, when compared to the commercial controls such as expanded polytetrafluoroethylene (ePTFE) and polyethylene terephthalate (PET). Furthermore, endothelial cells adhered, spread, and proliferate well on the nanotextile. Thus, this study demonstrates that the unique nanofibrous architecture of woven textiles aids in developing a novel biodegradable material, which meets the clinical standards of a vascular patch. Abstract : A woven polymeric nanotextile based on poly‐l ‐lactic acid (PLLA) and poly(caprolactone) (PCL), fabricated by electrospinning, is tested as a vascular patch substitute. The nanotextiles show improved mechanical properties and exhibit good hydrophilicity, protein adsorption, and hemocompatibility, in comparison to commercial controls such as polyethylene terephthalate (PET) and expanded polytetrafluoroethylene (ePTFE). The nanotextile also promotes enhanced endothelialization, suggesting its potential as a vascular patch.